Rate of force development during a handgrip task is correlated with the post-impact ball speed of the flat serve - Dobos, K.; Novak, D.; Tóth, J. P.; Ökrös, C. (Sports, 2024)
The aim of the present research was to test the hypothesis that rate of force development (RFD) during a handgrip task of the dominant arm in three different positions is associated with maximal post-impact ball speed of flat serve (PIBS). Altogether 23 elite junior boys (aged 14.84 ± 2.47 years; weight 59.51 ± 13.83 kg; height 170.47 ± 16.34 cm) tennis players participated in the study. To assess the maximal voluntary contraction (MVC) and RFD during the task, four handgrip tests and a serve test were applied to estimate PIBS. Spearman`s rank correlation showed a significant positive correlation between RFD of dominant arm in each three position and PIBS (r = 0.82-0.86; p < 0.001). A very large, significantly positive correlation was also found between MVC of the dominant arm and PIBS (r = 0.88; p < 0.01). The result of the present study indicated that rapid force generation of muscles in the forearm and wrist may probably play a role in the formation of a stable contact point, and it is in connection with PIBS. It is in contrast to the slow maximal force exertion that much rather characterizes the general strength state of players. Therefore, measurement of the RFD during a handgrip task is suggested in the testing session of the flat serve of junior tennis players.